Wavelets : theory and applications - Erlebacher, Gordon, 1957-; Hussaini, M. Yousuff; Jameson, Leland M. (ICASE/LaRC series in computational science and engineering., 1996)
1. Introduction to Wavelets and their Applications to Partial Differential Equations, L.M. Jameson. 2. Wavelets from Filter Banks, G. Strang. 3. Wavelets, Functions, and Operators, Ph. Tchamitchian. 4. Wavelets, Multiresolution Analysis, and Fast Numerical Algorithms, G. Beylkin. 5. Some Wavelet Algorithms for Partial Differential Equations, J. Liandrat. 6. Some Wavelet Algorithms for Turbulence Analysis and Modelling, J. Liandrat. 7. Wavelet Analysis of Fractals: from the Mathematical Concepts to Experimental Reality, A. Arneodo.